RAPID RECOGNITION OF REFERENCE SIGNAL DURING ITS DISTORTION BY NONLINEAR OBJECTS WITH EXPONENTIAL STATIC CHARACTERISTIC - Avramenko, V. V.; Shelehov І. V.; Zaretsky, M. O. (Radio Electronics, Computer Science, Control, 2017)
Context. Recognition of etalon signals distorted by device with unknown parameters of static characteristics is actual task for many practical problems. Moreover, addition system requirements for invariance to signal amplitude and for operativeness of recognition are relevant. Objective. The problem of operative recognition of etalon signal distorted by nonlinear device with exponential static characteristic is considered. А signal from given set of etalons come into input of a nonlinear object. It is necessary for the distorted signal at the output of the object recognized etalon on condition that characteristics of the non-linearity and amplitude of the input signal are unknown. It is assumed that the signal does not exceed the static nonlinear characteristics of the object area. Method. A method to solve the problem on the instantaneous values of the distorted signal at the output of the non-linear object is proposed. It is based on the use of disproportionate function value of the first order for numeric functions defined parametrically. If the two functions there is a proportional relationship, is calculated for these function disproportionate value of the first order is equal to zero for any value of the coefficient of proportionality. If the two functions have a proportional relationship, so disproportionate function is zero for any value of the coefficient of proportionality. Initially, hypothesis about the etalon signal of distorted signal is promoted. Then, both signals use for calculating disproportion function. Finally, if the hypothesis is confirmed, then disproportionate of etalon signal turns into zero, else the disproportionate is nonzero. Results. Computer modeling of recognition system for narrowband reference signals is performed. The results show that the system successfully detects slightly differ signals at different exponential characteristics parameters of nonlinear static object. Conclusions. The method can be used to recognition of weak etalon signals distorted by nonlinear object with static exponential characteristic an origin of coordinates under conditions where the parameters of nonlinearity and signal amplitude are unknown. In practice, these conditions are typical for remote control system when weakened or distorted control signals arrive at the input of p-n junction semiconductor of receiving device.